The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1109/tps.2008.920888
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protrusions on Cathodic-Arc-Attachment Mode in High-Pressure Arc Discharges

Abstract: Abstract-It is shown via computer simulations that a protrusion on a thermionic arc cathode may dramatically change the pattern of steady-state modes of current transfer. This happens through a bifurcation of a special type occurring at certain geometry of the cathode and may play a role in operation of electrodes of compact high-intensity discharge lamps.Index Terms-Arc attachment, arc cathode, bifurcation of current transfer, bifurcation theory, high-pressure arc. CONSIDERABLE advances in theoretical and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2008
2008
2009
2009

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
(6 reference statements)
1
8
0
1
Order By: Relevance
“…Presumably, some of these other modes can be described by means of the same model of nonlinear surface heating that has been successfully applied to the diffuse and spot modes. For example, this is presumably the case of the super-spot mode: it has already been mentioned above that this mode may be related to the change in the pattern of steady-state modes of current transfer caused by a protrusion, detected by simulations [109] performed in the framework of the model of nonlinear surface heating. In connection with the blue-core mode, one could think of the above-mentioned solutions with different branches of the function q(T w , U): a branch with low values of T e would describe the diffuse and spot modes and a branch with high T e would describe the blue-core mode.…”
Section: Other Topics Workmentioning
confidence: 92%
See 1 more Smart Citation
“…Presumably, some of these other modes can be described by means of the same model of nonlinear surface heating that has been successfully applied to the diffuse and spot modes. For example, this is presumably the case of the super-spot mode: it has already been mentioned above that this mode may be related to the change in the pattern of steady-state modes of current transfer caused by a protrusion, detected by simulations [109] performed in the framework of the model of nonlinear surface heating. In connection with the blue-core mode, one could think of the above-mentioned solutions with different branches of the function q(T w , U): a branch with low values of T e would describe the diffuse and spot modes and a branch with high T e would describe the blue-core mode.…”
Section: Other Topics Workmentioning
confidence: 92%
“…A protrusion on a thermionic arc cathode dramatically changes the pattern of steady-state modes of current transfer in certain cases, as shown by simulations [109]: it may happen that there is only one steady-state mode in a wide current range and this mode is spot-like. This finding may be related to the so-called super-spot mode observed in the experiment [110] and to observations [111] indicating that a protrusion on the front surface facilitates stable operation of the cathode in a mode with a spot.…”
Section: Other Topics Workmentioning
confidence: 93%
“…In the following sections, the bifurcations identified above will be discussed in some detail. Also discussed will be transcritical bifurcations {1D, 2D} and {2D, 2D} of second-order contact encountered in the modelling of glow discharge [33] and non-cylindrical arc cathodes [19,20], respectively.…”
Section: Identifying Bifurcations Encounteredmentioning
confidence: 99%
“…Numerical modelling of arc cathodes of shapes of industrial interest [19,20] revealed a possibility of dramatic changes in the pattern of steady-state modes of current transfer. As an example, figure 13(b) shows the temperature at the centre of the front surface of a cathode having the shape of a rod (cylinder) with a hemispherical tip.…”
Section: Transcritical Bifurcations Of Second-order Contactmentioning
confidence: 99%
See 1 more Smart Citation